Extraction efficiency, physicochemical properties and hypercholesterolemia-lowering capability of virgin avocado oil - Tan, Chin Xuan (2019)
Virgin avocado oil (VAO) has been touted as functional oil due to its high nutritional value and bioactive components. This study aimed to investigate the extraction efficiency and physicochemical properties of VAO extracted using green techniques [ultrasound-assisted aqueous extraction (UAAE) and subcritical CO2 extraction (SCO2)] as well as the hypercholesterolemia-lowering potential of VAO intake. The optimum UAAE parameters to produce the highest recovery of low free fatty acids VAO were 6 mL/g of water-to-powder ratio, 30 min of sonication time and 35c of sonication temperature. Oil yield obtained from solvent extraction (20.79%) was significantly greater (p<0.05) than SCO2 (16.97%) and UAAE (15.13%). Regardless of the extraction methods used, the major fatty acids in avocado oil were oleic (40.73- 42.32%), palmitic (28.12-34.48%) and linoleic (15.52-18.88%) acids whereas the major triacylglycerols in avocado oil were palmitoyl-dioleoyl-glycerol (22.48-23.01%) and palmitoyl-oleoyl-linoleoyl-glycerol (17.64-18.23%). Avocado oil extracted using SCO2 exhibited the strongest antioxidant capacity and contained two to four times greater levels of α- and ƴ-tocopherols than UAAE and solvent extraction. The hypercholesterolemia-lowering capability of VAO was assessed using diet-induced hypercholesterolemia rats. This in vivo study comprised five groups of rats, namely, normal diet control, high-cholesterol diet (HCD) control, HCD administrated with 450 mg/kg body weight VAO (HL), HCD administrated with 900 mg/kg body weight VAO (HH) and HCD administrated with 10 mg/kg body weight simvastatin (HS). Highdensity lipoprotein cholesterol level was significantly increased (p<0.05; 45% for HL, 77% for HH and 23% for HS) and the total triacylglycerols level was significantly reduced (p<0.05; 42% for HL, 58% for HH and 52% for HS) in the VAO- and simvastatin-treated rats when compared with their respective baseline results. On the other hand, low-density lipoprotein cholesterol was significantly reduced (p<0.05) in the HH (31%) and HS (49%) when compared with their respective baseline results. Results of the metabolomics study revealed that VAO intake could partially recover the metabolism dysfunction induced by hypercholesterolemia mainly via lipid, energy, amino acid and gut microbiota metabolism. In conclusion, VAO has the potential to be utilized as functional oil to lowering hypercholesterolemia.